2001
DOI: 10.1038/35093166
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of temperate plants in east Asia

Abstract: The exceptionally broad species diversity of vascular plant genera in east Asian temperate forests, compared with their sister taxa in North America, has been attributed to the greater climatic diversity of east Asia, combined with opportunities for allopatric speciation afforded by repeated fragmentation and coalescence of populations through Late Cenozoic ice-age cycles. According to Qian and Ricklefs, these opportunities occurred in east Asia because temperate forests extended across the continental shelf t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
347
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(382 citation statements)
references
References 6 publications
26
347
7
1
Order By: Relevance
“…China Sea (ECS) to the Korea/Tsushima Strait (KS) (Harrison et al 2001). Thus, the current distribution and genetic structure of warm-temperate plant species in CJK are considered to be closely associated with the formation of that historical land bridge (see review by Qiu et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…China Sea (ECS) to the Korea/Tsushima Strait (KS) (Harrison et al 2001). Thus, the current distribution and genetic structure of warm-temperate plant species in CJK are considered to be closely associated with the formation of that historical land bridge (see review by Qiu et al 2011).…”
mentioning
confidence: 99%
“…Pollen records and some molecular data have indicated that those forests disappeared from the Peninsula during the LGM but have, since then, been colonized from southern refugia of China and/or Japan (Chung et al 2013(Chung et al , 2014Harrison et al 2001). However, other molecular evidence has implied that refugia existed within the Korean Peninsula during the LGM and that re-colonization from Southern Japan also occurred (Lee et al 2014).…”
mentioning
confidence: 99%
“…In the west of the region, the uplift events of the Himalayas and Hengduan Mountains during the last few million years are reported to have caused drastic habitat fragmentation and heterogeneity which played important roles in promoting inter-and intraspecific divergences Wang et al, 2014). In the east of the region, fluctuations in sea level of the East China Sea have also been shown to have provided abundant opportunities for population fragmentation and allopatric speciation to occur (Qian and Ricklefs, 2000;Harrison et al, 2001;Qiu et al, 2009aQiu et al, , b, c, 2011. Additionally, it is well known that climate change plays a critical role in shaping the distribution of plants (Harrison et al, 2001;Qiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the east of the region, fluctuations in sea level of the East China Sea have also been shown to have provided abundant opportunities for population fragmentation and allopatric speciation to occur (Qian and Ricklefs, 2000;Harrison et al, 2001;Qiu et al, 2009aQiu et al, , b, c, 2011. Additionally, it is well known that climate change plays a critical role in shaping the distribution of plants (Harrison et al, 2001;Qiu et al, 2011). The range dynamics in response to past climate change have been assessed based on ecological niche modelling (ENM) for a limited number of plants in the SJFR, such as Cercidiphyllum (Qi et al, 2012), Kalopanax septemlobus (Sakaguchi et al, 2012) and Tetrastigma hemsleyanum (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Refugia created by microclimatic variations provided some protection, and habitat fragmentation caused new speciation and diversification (Hewitt 2000; Harrison et al 2001; Yang 2005). As indicated by the current published data, distribution areas of morels in North America and Europe are concentrated on the west and east coasts and the Mediterranean coast, which have been recognized as probable refugia in several studies (Hewitt 2000; Soltis et al 2006).…”
Section: Evolutionary History Of Morchellamentioning
confidence: 99%